Azoreductases in drug metabolism. (2nd September 2016) - Ryan, Ali
Abstract : Azoreductases are flavoenzymes that have been characterized in a range of prokaryotes and eukaryotes. Bacterial azoreductases are associated with the activation of two classes of drug, azo drugs for the treatment of inflammatory bowel disease and nitrofuran antibiotics. The mechanism of reduction of azo compounds is presented; it requires tautomerisation of the azo compound to a quinoneimine and provides a unifying mechanism for the reduction of azo and quinone substrates by azoreductases. The importance of further work in the characterization of azoreductases from enteric bacteria is highlighted to aid in the development of novel drugs for the treatment of colon related disorders. Human azoreductases are known to play a crucial role in the metabolism of a number of quinone‐containing cancer chemotherapeutic drugs. The mechanism of hydride transfer to quinones, which is shared not only between eukaryotic and prokaryotic azoreductases but also the wider family of NAD(P)H quinone oxidoreductases, is outlined. The importance of common single nucleotide polymorphisms (SNPs) in human azoreductases is described not only in cancer prognosis but also with regard to their effects on the efficacy of quinone drug‐based cancer chemotherapeutic regimens. This highlights the need to screen patients for azoreductase SNPs ahead of treatment with these regimens. Linked Articles: This article is part of a themed section on Drug Metabolism and Antibiotic Resistance in Micro‐organisms. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.14/issuetoc